CORD AROUND NECK IN SINGLETON TERM PREGNANCIES AND ITS OUTCOME: Cord Around Neck - Sajjad, Rabia; Mushtaq, Mamoona; Mustafa, Nilofer (Pakistan Armed Forces Medical Journal, 2014)
Objectives: To enlist the complications with nuchal cord in singleton term pregnancies and to determine maternal and fetal outcome in singleton term pregnancies.Design: Descriptive study.Place and duration of study: The study was carried out at Gynaecology and Obstetric department Combined Military Hospital Quetta from Nov 2007 to May 2008.Patients and methods: One hundred women irrespective of parity with healthy, singleton term pregnancy and cephalic presentation, labouring or not labouring, were selected from outpatient department. A total of 41 patients were booked with Doppler ultrasound done in antenatal period. Other 59 were poorly booked and diagnosed with cord around neck by clinical criteria e.g. high head at term, fetal distress, meconium discharge, slow progress in labour leading to prolonged labour. All patients signed well informed written proforma regarding study and its outcome. Vigilant feto maternal monitoring was done during labour. All events during labour were mentioned in proformas which were attached with patients case notes. Data was interperated in term of frequency and percentages.Results: Complications with cord around neck found were still birth 3%, fetal distress 15%, intrauterine death 1%. Prolonged labour was seen in 14%, Meconium discharge in 5%, and high presenting part was found in 11% of cases. Maternal outcome were elective caesarean section in 6%, emergency caesarean-section in 32%, spontaneous vaginal delivery in 54% and instrumental vaginal delivery in 8% of the cases. Different fetal outcomes seen were intrauterine death, stillbirth in 1%, and 3% patients respectively. Regarding neonatal outcome, 31% stayed in neonatal intensive care unit (NICU) for less than 48 hours, 69% stayed in NICU for more than 48 hours out of which 4% had early neonatal deaths (ENND). Fifty nine percent patients detected and suspected during labour were with, high head, slow progress in labour, decreased fetal movements, intra partum fetal distress, meconium stained labour. Cord length was measured, 60 cm in 28%, 53 cm in 21%, 74 cm in 51% of patients. Longer length of cord (74 cm) was seen in patients ended up into emergency cesarean.Conclusion: Cord around neck can be delivered vaginally if monitored carefully. Immediate action is required in case of any complication to get good maternal and fetal outcome and to avoid morbidity and mortality with cord around neck.